The relationship between corporate social responsibility and firm performance: evidence from Jordan - Moawiah Awad Alghizzawi; Mayada A. Youssef; Mohammed Abu Zraiq; Moataz Elmassri (Cogent Business & Management, 2022)
This study aims to investigate the relationship between corporate social responsibility (CSR) and Jordanian firm performance. CSR is measured using three dimensions: philanthropy, community, and environment. Meanwhile, firm performance is measured by two accounting-based measurements; Return on Assets (ROA) and Return on Equity (ROE). We employ the legitimacy theory as a theoretical perspective for the current study. The data included 200 observations of 100 service and industrial Jordanian companies listed on the Amman Stock Exchange. SPSS is used for data analysis. The results indicate a significant positive association between community and environment with both ROA and ROE. However, Philanthropy does not significantly affect ROA and ROE. Additionally, Jordanian companies seem to apply "form" when it comes to philanthropy. Organizational legitimacy is their principal management objective, not improving philanthropy disclosure practices. However, regarding community and environmental disclosures, firms seek organisational legitimacy by adopting substantive changes to the information content of such parameters. This study's contributions are twofold. First, we expand the literature by exploring the effect of CSR disclosure on firm performance in an emerging economies context. Secondly, to our knowledge this is the first study that examines whether managers use CSR disclosures as symbolic or substantive actions to gain organisational legitimacy. As a practical implication of this study, investors should consider the companies' community and environmental CSR activities when making investment decisions. Future research may include the mediating or moderating effect of other variables on the relationship between CSR and firm performance.
Keywords: 650; community; corporate social responsibility; environment; firm performance; Jordan; Legitimacy theory; Philanthropy